THE PENALTY FOR THE CORRUPTOR IN THE SOCIOLOGICAL PERSFEKTIF - Syamsul Haling (Indonesia Prime, 2016)
Sociological perfective in the many offer social sanctions can be applied in corrupt behavior result. The idea of social sanctions was proposed as a reaction against the growing number of corrupt behavior difficult resolved only through national and international legal instruments. It is time the exact type of sanctions was found to tackle corrupt behavior that are already classified as extraordinary crimes. Some ideas proposed as social sanctions to eradicate corrupt behavior i.e. criminal sanctions established on the basis of social stratification, hint herself and family corruptor, no corpse prayer corruptor before is no guarantee of the financial returns of the State by the family of the perpetrator, serving in the corruptor's face television and penalties for disseminating the corruptor after death and as sanctions ultimatum remedied every corruptor will be charged all his deeds before God after death.